New diterpenoids from the stems of Euphorbia antiquorum growing in Vietnam. Issue 2 (17th January 2022) - Tran, Thanh-Nha; Sichaem, Jirapast; Nguyen, Van-Kieu; Nguyen, Huu-Hung; Cao, Truong-Tam; Nguyen, Thi-Phuong; Vo, Van-Giau; Niamnont, Nakorn; Nguyen, Ngoc-Hong; Duong, Thuc-Huy
Abstract: Phytochemical analysis of Euphorbia antiquorum stem extracts afforded two new ent- atisane compounds, ent- 3 α -acetoxy-16 β, 17, 18-trihydroxyatisane (1 ) and ent- 3 α, 14, 16 β, 17-tetrahydroxyatisane (2 ) together with three known compounds, 20-deoxy-16-hydroxyingenol (3 ), ent- 14[S], 16 α, 17-trihydroxyatisan-3-one (4 ), and agallochaol C (5 ). Their structures were elucidated by spectroscopic data analysis and comparison with published NMR data. Compounds 1–5 were evaluated for α -glucosidase inhibition and cytotoxicity. Compounds 1, 4, and 5 revealed significant inhibitory activity against α- glucosidase with the IC50 values of 119.9, 135.5, and 134.3 µM, respectively. None showed activity in cytotoxicity assay. Abstract : UF0001